Effect of inoculants on the fermentation of wheat, alfalfa, and sorghum silages - Bolsen, K.; Smith, R.; Ilg, H.; Fung, Daniel Y. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Results from three laboratory silo experiments showed that four commercial silage inoculants increased fermentation rate, particularly during the first 4 days of the ensiling process. The effects of the additives on pH drop and lactic acid production were greater in wheat and alfalfa than in forage sorghum.
Keywords: Beef; Fermentation; Wheat; Alfalfa; Sorghum silage